Controlling merchandise inventory using the economic order quantity multi-item discount model method using Odoo software at UD. Ridho - Khairul Anshar; Subhan A. Gani; Nurbayyinah Rangkuti (TEKNOSAINS : Jurnal Sains, Teknologi dan Informatika, 2024)
UD. Ridho is a business based in Jl. Sudirman Pekan Dolok Masihul, Dolok Masihul District, Serdang Bedagai Regency, North Sumatra, deals in the sale and purchase of goods. The business had an accumulation of surplus inventory, or overstock, which damaged the goods and kept them from going bad. resulting in total losses of Rp 154,104,00 from January 2023 to June 2023. Orders are placed by UD. Ridho for goods from five vendors. The EOQ Multi Item Model Discount Method is applied in this study using the Odoo software. The EOQ Multi-Item Discount Model is a technique for optimizing inventory costs by placing orders for commodities based on economic order amounts from many suppliers. Product categories offered by UD. Ridho Sugar, rice, wheat flour, instant noodles, soy sauce, detergent, salt, water, and edible oil are the ingredients of UD. Ridho. The discount model is applied to goods that receive a discount from the seller according to the quantity of goods bought. Instant noodles, rice, detergent, edible oil, and aqua are the products that are discounted. Applying the multi-item discount model approach with economic order quantity at UD. Ridho was able to save Rp 21,893,660, or 3.02% of the total amount. The Odoo software, which has three modules—inventory, purchasing, and sales orders—can be used with this paradigm to construct an inventory management application